Modernization of the regulation of the Verkhovna Rada of Ukraine in the system of normative guidelines for parliamentary reform - Linetskyi S. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The purpose of the study is to determine the main directions of modernization of the Regulation of the Verkhovna Rada of Ukraine (hereinafter referred to as the Regulation) in the context of the key guidelines of parliamentary reform at the current stage of Ukraine’s development. Method. The methodology includes a comprehensive analysis and generalization of available scientific and theoretical material and the formulation of scientific and legal conclusions and recommendations. The following methods of scientific knowledge were used during the research: dialectical, analytical-synthetic, hermeneutic, systemic-structural, prognostic. The results. In the process of research, it was found that the optimal way to modernize the Regulation is to focus on the system of normative guidelines for parliamentary reform, which reflect its objective and natural nature. It has been established that the system of such guidelines is provided for in the Report and Roadmap presented by the Evaluation Mission of the European Parliament on internal reform and increasing the institutional capacity of the Verkhovna Rada of Ukraine. Such benchmarks need their consistent and objective disclosure when adjusting the norms of the Regulation taking into the state of parliamentary procedures. Through a systematic analysis of normative material and legislative developments, the specifics of each of the identified methods of modernization of the Regulation under modern conditions were revealed. Originality. In the process of research, it was established that the modernization of the Regulation should take place on the basis of scientific ideas about the system of normative guidelines of the parliamentary reform, which reflect its objective and natural character. The requirements of constitutionalization, Europeanization, digitalization, consensualization, as well as ensuring regulatory continuity and adaptation to changes are identified as key. Practical significance. The results of the research can be used both during the current (preparation of current changes to the Regulation) and during prospective (planning of comprehensive changes to the Regulation) legislative work on improving the Regulation.